Trust requirements for ecommerce website - Che Hussin, Ab. Razak; Mohamed Dahlan, Halina; Bahari, Mahadi (2003)
The presence of attributes of trust in eCommerce websites is essential for gammg consumer confidence. However, until now, it is unknown which trust attributes are valued more by consumers. Furthermore, this scenario may lead to wasting consumer's time in searching and e\'aluating trust attributes. The purpose of this paper is to describe the specification of a trust attributes that based on Informational-based and Functional-based. The paper emphasises the need for trust attributes in eCommerce websites by examining five models of trust. Four trust dimensions. namel~ 'merchant trust'. 'content trust'. 'product trust'. and' proccss trust' are proposed based on trust development stages.